IMPLEMENTASI STANDAR PELAYANAN PUBLIK BAGI MAHASISWA PENYANDANG DISABILITAS BERDASARKAN PERATURAN MENTERI RISET, TEKNOLOGI DAN PENDIDIKAN TINGGI NOMOR 46 TAHUN 2017 DI UNIVERSITAS RIAU - Permadi, Eko; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Minister of Technology and Higher Education Regulation Number 46 Year 2017 concerning Special Education and Special Services Education in Higher Education becomes a standard of service for students with disabilities. Basically the implementation of public policy is aimed at how the ideals in a legal product can be realized properly. The University of Riau as a public service provider in the field of higher education is in fact still not optimally realizing the fulfillment of Economic, Social and Cultural Rights. There are several problems that still need to be fixed. This type of research is empirical / sociological legal research with observation, interview, questionnaire and literature study data collection techniques. Qualitatively analyze data and use deductive thinking methods. The results showed that the implementation of public service standards for students with disabilities at the University of Riau was not satisfactory. Many service standards starting from the admission of new students, facilities and infrastructure, disability service units and financing have not been met by the University of Riau. There are several factors that become obstacles such as service providers that have not made a legal basis for its implementation in the internal environment, construction of facilities and infrastructure has not been a priority and from students with disabilities do not know what their rights are while studying at Riau University. Proposed improvement of public services is very important so that students with disabilities can study comfortably and easily in the campus environment.